Analisis Kesalahan Berbahasa pada Talk Show Kick Andy yang Berjudul “Sempurna di Mata Tuhan” - Munsi, Mia Fatimatul; Ismawar, Ismawar; Fitriyanti, Fitriyanti (Universitas Mathla'ul Anwar Banten, 2024)
This research is part of the integration of the Language Error Analysis course with scientific research. The aim of this study is to describe language errors in the Kick Andy talk show episode titled “Perfect in the Eyes of God.” This study employs a qualitative descriptive method, with data collected using the observation and note-taking technique. The collected data were analyzed to identify types of language errors and sentence inefficiencies that appeared in the dialogue between the host and the guests. The findings reveal 17 instances of language errors, including the use of non-standard words and sentence inefficiencies. Some examples of non-standard words found in the talk show include nggak, udah, cuman, temen-temen, kenapa, nampak, teger, and others. Meanwhile, sentence inefficiencies include a lack of cohesive ideas, structural incompatibility, and excessive word use. Such language errors can affect the clarity and comprehension of messages delivered to the audience. Therefore, this study is expected to provide insights into the importance of using proper and effective language in public communication, especially in television media, which has a broad reach in society.